RELAYOUT GUDANG FITTING PIPA DENGAN METODE SHARED STORAGE DI PT. TJAKRINDO MAS - Kharisma, Bella; Satoto, Handy Febri (J-ENSITEC, 2024)
This analysis illustrates how changes in warehouse structure affect the smooth operation of a company or factory. At PT. Tjakrindo Mas, there is an irregular arrangement of finished product storage. causing a pile of goods that are not in accordance with the type so that during the retrieval process using a forklift there are difficulties due to the area that is not large so that it must be assisted with a hand pallet to carry the product to a wider area so that it can be reached by a forklift. That way it will waste a lot of time just because of the difficulty of wanting to transport goods. The method to be applied in the storage arrangement is the shared storage method, organised by placing finished products based on the FIFO (First In First Out) principle. This will minimise transport time as well as ensure efficient use of space.